La fabrique sociale : autonomisation et légitimation dans le domaine de l’information de santé - Adrian Staii (Netcom)
More than one third of the French population searches health information on the Internet, a trend which kept growing over the last years. Traditional authorities (health professionals, experts, etc.) have to deal with patients who gather information and build illness representations from alternative sources (discussion groups, blogs, associative websites, etc.). In a society where individuals are constantly being asked to support themselves, they need to feel involved in their healthcare. The evolutions presently taking place in the field of health information are connected to larger social trends and they unveil their full meaning when linked to these structural conditions: the renewal of the confidence in the expert systems, the enhancement of social autonomy and the enlargement of the well-being culture. This paper focuses on the analysis of these wide social trends. Their impact on health information will be discussed in the last part of the paper through the presentation of the findings of an empirical research on health discussion groups.